VALIDITAS DAN RELIABILITAS INSTRUMEN PENILAIAN PROGRAM BAHASA INGGRIS GRUP 5 FAKULTAS EKONOMI BISNIS ISLAM PUSAT PENGEMBANGAN BAHASA IAIN PADANGSIDIMPUAN T.P. 2018/2019 - ZULPAN (Jurnal Sinar Edukasi, 2020)
This research is aimed to describe validity and reliability of instrument on English assessment at Language Centre of IAIN Padangsidiimpuan Program. The descriptive quantitative is kind of research method that used on this research. Subject of this research is the group 5 of Economy of Islamic Business Faculty at IAIN Padangsidimpuan that consisted with 24 students. Data collected from result of reading, writing, listening, speaking, and structure of the students. Method of analysis data is taken by using validity and reliability tests through software SPPS version 16. The result showed that all of indicators on mid-semester test were valid and the instrument is reliable meanwhile in the final-semester test showed reading, writing, listening, speaking were not valid and the structure one was valid and the instruments were not reliable.